Evaluation of the GENE-UP® Listeria monocytogenes Method for the Detection of Listeria monocytogenes in a Variety of Foods and Select Environmental Surfaces: Collaborative Study, First Action 2019.11. (21st July 2020) - Johnson, Ronald; Mills, John; Pittet, Jean-Louis; Mathia, Olivier; Bird, Patrick; Nelson, Maria
Abstract: Background: The GENE-UP ® Listeria monocytogenes 2 (LMO 2) assay ( Performance Tested Method SM 121804) uses real-time PCR technology and a proprietary detection platform, the GENE-UP Thermocycler, to detect Listeria monocytogenes in a variety of foods and environmental surfaces. Objective: The purpose of this validation was to evaluate the method's interlaboratory performance and submit the result to AOAC INTERNATIONAL for adoption as First Action Official Method SM for the detection of Listeria monocytogenes in a variety of foods and select environmental surfaces. Method: The GENE-UP method was evaluated in a multi-laboratory study as part of the AFNOR NF VALIDATION certification process using unpaired test portions for one food matrix, full-cream goat milk cottage cheese (8.4% fat). The candidate method was compared to the ISO 11290-1/Amd.1:2004 reference method. Sixteen participants from 15 laboratories throughout the European Union participated. Three levels of contamination were evaluated: a non-inoculated control level (0 CFU/test portion), a low inoculum level (∼2 CFU/test portion), and a high inoculum level (∼10 CFU/test portion). Data from the study were analyzed according to the Probability of Detection (POD) statistical model as presented in the AOAC validation guidelines. Results: The dLPODC values with 95% confidence interval for each comparison were; -0.02 (-0.07, 0.03), -0.08 (-0.31, 0.16), and 0.00 (-0.03, 0.03) for the non-inoculated, low, and high contamination levels, respectively. Conclusions: The dLPODC results demonstrate no difference in performance between the candidate method and reference method for the matrix evaluated. Highlights: The GENE-UP LMO method demonstrated accuracy and precision in detecting and discerning L. monocytogenes from other Listeria species.